PENGARUH KEMISKINAN, PENGANGGURAN, DAN ANGKA PARTISIPASI KASAR TERHADAP INDEKS PEMBANGUNAN MANUSIA DI INDONESIA TAHUN 2014-2023 - Amin, Moch. Fariz Al; Restikasari, Wenny (Jurnal Ilmu Ekonomi, 2024)
This research aims to determine the effect of the independent variables, namely Poverty Percentage, Unemployment Percentage, and Gross Participation Rate on the dependent variable, namely the Human Development Index in the period 2014-2023. This research uses a quantitative approach and uses secondary data obtained from the websitewebsite Central Bureau of Statistics. The method used is Panel Data Analysis. The results of this research state that the three independent variables mentioned above, namely Unemployment and Gross Participation Rate, have a significant positive effect, while the Poverty variable has a significant negative effect on the Human Development Index in Indonesia in 2014-2023.